Managing Change - Case Study of Al Asayel Primary School - Alsuwaidi, Alyazia; Alanasari , Haya; Almarzooqi , Mariam; Kalban , Shamsa (European Journal of Business and Strategic Management, 2023)
Purpose: The paper aims to study the change process strategies and approaches followed by Al Asayel School administration and their change agent, Alef Education, to transform the school from being a traditional primary school to a smart technology-based one. This was performed through tackling the change process and its impact on different stakeholders, and highlighting the importance of managing change successfully, to better deliver a successful change journey. Methodology: To further understand the change process and its impact on Al Asayel School - Abu Dhabi, an interview was held with the school's stakeholders who are: The school's principal, a primary school teacher, and a primary school student. The responses obtained were then supported with secondary research where literature and models were used to better illustrate and analyze the findings. Findings: The study showcases a steady and gradual change process initiated by Alef Education. With the willingness, dedication and cooperation of Al Asayel School administration, teachers and students, the change process was successfully implemented. Regardless of minor issues, the initiator responded quickly, was constantly available to provide solutions before, during and after the change. The level of resistance of the different stakeholders was identified, along with how the school and its change agent dealt with it. The analysis showcased that Al Asayel School's principal and Alef Education implemented Lewin's change model successfully and communicated the change with teachers, students and parents in a motivational manner, through focusing on explaining all change aspects while addressing and easing raised concerns. This aided in controlling resistance to change and guaranteeing a successful transformation. Unique Contribution to Theory, Practice and Policy: The paper showcases a unique case that broadens our understanding of the usage of Lewin's change model by Alef Education to education in the UAE through investigating the first school that implemented this change and how they managed to adapt while inspiring schools to adopt new platforms and educational technology.